2021
DOI: 10.1002/ardp.202100201
|View full text |Cite
|
Sign up to set email alerts
|

Phthalazine‐based VEGFR‐2 inhibitors: Rationale, design, synthesis, in silico, ADMET profile, docking, and anticancer evaluations

Abstract: In the designed compounds, a new linker was inserted in the form of fragments with verified VEGFR‐2 inhibitory potential, including an α,β‐unsaturated ketonic fragment, pyrazole, and pyrimidine. Also, new distal hydrophobic moieties were attached to these linkers that are expected to increase the hydrophobic interaction with VEGFR‐2 and, consequently, the affinity. These structural optimizations have led us to identify the novel dihydropyrazole derivative 6e as a promising hit molecule. All the new derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…Anastrozole containing a 1,2, 4-triazole ring is used in the treatment of postmenopausal women with estrogen-responsive breast cancer. [24] On the basis of the earlier findings and in continuation of our previous research in anticancer agents, [25][26][27][28][29][30][31][32][33][34][35] especially DNA intercalators, [36][37][38][39] we reported herein DNA-binding and docking studies of a new series of [1,2,4]triazolo [4,3-c]quinazoline derivatives as anticancer agents.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Anastrozole containing a 1,2, 4-triazole ring is used in the treatment of postmenopausal women with estrogen-responsive breast cancer. [24] On the basis of the earlier findings and in continuation of our previous research in anticancer agents, [25][26][27][28][29][30][31][32][33][34][35] especially DNA intercalators, [36][37][38][39] we reported herein DNA-binding and docking studies of a new series of [1,2,4]triazolo [4,3-c]quinazoline derivatives as anticancer agents.…”
Section: Introductionmentioning
confidence: 84%
“…On the basis of the earlier findings and in continuation of our previous research in anticancer agents, [ 25–35 ] especially DNA intercalators, [ 36–39 ] we reported herein DNA‐binding and docking studies of a new series of [1,2,4]triazolo[4,3‐ c ]quinazoline derivatives as anticancer agents.…”
Section: Introductionmentioning
confidence: 90%
“…The synthesis was initiated by cyclocondensation of 2-benzoylbenzoic acid 1 with hydrazine hydrate to afford the corresponding 4-phenylphthalazin-1(2H)-one 2, which underwent chlorination by reaction with phosphorous oxychloride to afford 1-chloro-4-phenylphthalazine 3 following the reported procedures. [20,52] The chloro derivative 3 was heated under reflux with the methyl 4-aminobenzoate to afford the corresponding methyl ester derivative 4. On the contrary, the ester derivative 4 was heated under reflux with hydrazine hydrate to yield the corresponding hydrazide 5 (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…Here, we present DNA binding and docking studies of a new series of [1,2,4]triazolo[4,3‐c]quinazoline derivatives as anticancer agents, based on our earlier study in anticancer drugs, [ 8–22 ] especially DNA intercalators. [ 20,23–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present DNA binding and docking studies of a new series of [1,2,4]triazolo [4,3-c]quinazoline derivatives as anticancer agents, based on our earlier study in anticancer drugs, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] especially DNA intercalators. [20,[23][24][25][26] Intercalators interact with the DNA double helix reversibly.…”
mentioning
confidence: 99%